The usefulness of financial reporting for internal decision-making in portuguese municipalities - Nogueira, Sónia P. (2013)
The purpose of this paper is to analyse the perception of internal users regarding the usefulness of municipal financial reporting in the context of decision-making in Portuguese Local Administration. This research is quantitative and positive, based on a cross-section analysis through online application of a questionnaire to decision-makers (politicians and technicians) of the 308 Portuguese municipalities. The approach is based on the information usefulness paradigm. Results indicate a high usefulness for decision-making of the municipal financial reporting, in its current form and content. However, this usefulness would increase if information, other than what is mandatory, were introduced. In general, the two different groups of decision-makers, politicians and technicians, behave somewhat differently, regarding the usefulness financial reporting holds for them. Technical decision-makers consider it of greater value. There is no statistical evidence showing that there is a link between the training area and professional experience of the internal decision-makers and the usefulness of municipal financial reporting. Both types of users show a preference for the information set within the budgetary accounts, although accrual-based information also proved to be of very high value. This study has important repercussions on internal decision-makers concerning the usefulness of municipal financial reporting. Particularly, the general approach towards reporting usefulness could become a solid work basis for the regulatory bodies to enhance the current reporting model in the light of its suitability for internal decision-making.